2020
DOI: 10.1111/trf.15918
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and serological patterns of COVID‐19 convalescent plasma donors: optimal donors and timing of donation

Abstract: BACKGROUND The lack of effective treatments against the 2019 coronavirus disease (COVID‐19) has led to the exploratory use of convalescent plasma for treating COVID‐19. Case reports and case series have shown encouraging results. This study investigated SARS‐CoV‐2 antibodies and epidemiological characteristics in convalescent plasma donors, to identify criteria for donor selection. METHODS Recovered COVID‐19 patients, aged 18‐55 years, who had experienced no symptoms fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
54
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 26 publications
11
54
5
1
Order By: Relevance
“…Protective specific antibodies like IgG produced by B cells after infection with the virus, help block the virus from entering the host cells, as well as defend against viral reinfection. SAR-CoV-2 virus is enveloped with four structural proteins which serve as targets for antibodies [11,20,21], and uses its spike glycoprotein, a main target for neutralization antibody, to bind its receptor and mediate membrane fusion and virus entry [21]. The hypothesis is that administration of convalescent plasma containing such antibodies may mediate viral neutralization [22] by inhibiting viral replication and blunting pro-inflammatory endogenous antibody response [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Protective specific antibodies like IgG produced by B cells after infection with the virus, help block the virus from entering the host cells, as well as defend against viral reinfection. SAR-CoV-2 virus is enveloped with four structural proteins which serve as targets for antibodies [11,20,21], and uses its spike glycoprotein, a main target for neutralization antibody, to bind its receptor and mediate membrane fusion and virus entry [21]. The hypothesis is that administration of convalescent plasma containing such antibodies may mediate viral neutralization [22] by inhibiting viral replication and blunting pro-inflammatory endogenous antibody response [23].…”
Section: Discussionmentioning
confidence: 99%
“…Information on immune response to SARS-CoV-2 and duration is rather limited. Studies suggest thatt IgM expression is concurrent with IgG expression and both antibodies are associated with a high degree of variability in patients who test positive for the virus [11]. Li et al [11] showed that in 49 potential donors, IgG antibodies increased after 4 weeks from the onset of SARS-CoC-2 symptoms, while in another study these antibodies decreased in 2-3 months after the infection [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be suggested that this high rate was due to the exposition to con rmed cases, but leaving time enough to develop a robust humoral IgG response 24 . In fact, plasma from COVID-19 convalescent patients to be used as potential treatment against the infection, show signi cantly higher anti-SARS-CoV-2 titers after more than 42 days from symptom onset to plasma donation 25 . For those symptomatic subjects of our cohort, at least 14 days after the end of symptoms were required before performing the test with an average time gap of more than 40 days.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Desde el punto de vista de los bancos de sangre, es posible establecer el perfil del donante idóneo: paciente recuperado de infección por SARS-CoV-2, diagnosticado mediante hisopado nasofaríngeo con técnica de biología molecular (RT-PCR), captado idealmente a los 28 días del inicio de los síntomas, que cuente con una segun-da prueba molecular negativa al momento de la donación, obtener el componente mediante procedimiento de aféresis, y en términos generales debiendo cumplir con los criterios de la legislación nacional. 17 En resumen, aún con lo controversial del procedimiento, mantiene un lugar importante en la terapéutica de agentes infecciosos nuevos, ya que no hay otra alternativa que posibilite la atención específica fuera de las medidas generales de sostén. La inmunoterapia pasiva llegó para quedarse.…”
Section: Eficacia Y Seguridad Del Plasma De Convalecientesunclassified